Multidimensional analysis of screening results of deafness susceptibility genes in 3066 newborns of different altitudes and nationalities in Xining, Qinghai(ISRCTN89197487) - Benhong Ren; Yazhen Wu; Wenyuan Gan; Qingping Zhang; Dandan Yang; Wenjun Cao; Xiaoli Zhang; Yuan Jiang; Ying Zhang; Bin Guo; Yongxia Tie; Jiannan Liu; et al. (PLoS ONE, 2026)
Objective In Xining City, Qinghai Province, which is located in a high-altitude hypoxic environment, this study employs high-throughput sequencing technology to conduct large-scale deafness-related gene screening among newborns. It aims to assess the carrier rate and variant types of deafness-related genes in local newborns; and based on different genotypic characteristics, provide targeted health education and clinical guidance to the parents of children with deafness, with the goal of achieving early diagnosis, early prevention, and early intervention of deafness. At the same time, this study also provides scientific basic data support for deafness prevention and treatment-related research in Qinghai Province. Methods From March 2023 to March 2025, the research team of the Affiliated Hospital of Qinghai University strictly abided by ethical norms. With the full informed consent of the participants, the team systematically and continuously collected heel blood samples from multi-ethnic newborns living in areas at different altitudes, and successfully obtained 3,615 complete blood samples required for the study. Subsequently, high-throughput sequencing technology was applied to detect these samples, and accurate data on deafness susceptibility-related genes were obtained. During the analysis phase, the research team took altitude (low altitude, medium altitude, high altitude), ethnicity (Tibetan, Hui, Han, Salar, Tu, etc.), and genotype (15 loci of 4 common deafness-causing genes: GJB2, SLC26A4, mitochondrial 12SrRNA, and GJB3) as the core dimensions. By comprehensively using statistical analysis and bioinformatics methods, a systematic multi-dimensional analysis was conducted to deeply explore the association characteristics between different factors and the carriage of deafness susceptibility genes. Results This study collected a total of 3,615 cases of newborn blood spot specimens. After excluding 549 cases of substandard specimens, a valid screening cohort of 3,066 newborns was eventually formed. Within this valid cohort, 165 carriers of deafness-susceptible genes were identified, with an overall carriage rate of 5.38%. Stratified analysis by altitude showed that: in medium-altitude areas (with a sample size of 2,319 cases), 132 carriers were detected, corresponding to a carriage detection rate of 5.69%; in high-altitude areas (with a sample size of 742 cases), 33 carriers were detected, with a carriage detection rate of 4.45%. Statistical analysis indicated that the carriage detection rate of deafness-susceptible genes among newborns in high-altitude areas was significantly lower than that in medium-altitude areas. Genotyping data showed: GJB2 gene: A total of 73 mutations (2.38%) were detected, with the 235 del C mutation site being the most common, accounting for 67.12% of the total mutations in this gene. Among them, 58 cases were detected in medium-altitude areas and 15 cases in high-altitude areas, accounting for 20.55% (15/73) of the total GJB2 gene mutations. SLC26A4 gene: A total of 67 mutations (2.19%) were detected, with the IVS7−2 mutation site having the highest frequency, accounting for 47.76% of the total mutations in this gene. Among them, 59 cases were detected in medium-altitude areas and 8 cases in high-altitude areas, accounting for 11.94% (8/67) of the total SLC26A4 gene mutations. Mitochondrial 12S rRNA gene: A total of 33 mutations (1.08%) were detected, with the 1555 A > G mutation site being the main one, accounting for 96.97% of the total mutations in this gene. Among them, 25 cases were detected in medium-altitude areas and 8 cases in high-altitude areas, accounting for 24.24% (8/33) of the total mitochondrial 12S rRNA gene mutations. GJB3 gene: Only 1 rare mutation (0.03%) was detected at the 538 C > T site, and no such mutation was found in high-altitude areas. Analysis of the ethnic distribution of the 3,066 neonates showed: Han ethnicity: A total of 1,983 cases, with 115 cases detected (5.80%), accounting for 69.70% of all carriers. Hui ethnicity: A total of 476 cases, with 24 cases detected (5.04%), accounting for 14.55% of all carriers. Tibetan ethnicity: A total of 535 cases, with 24 cases detected (4.49%), accounting for 14.55% of all carriers. Mongolian ethnicity: A total of 24 cases, with 2 cases detected (8.33%), accounting for 1.21% of all carriers. Conclusion 1. Overall level: The overall carriage rate of deafness susceptibility genes in neonates from Xining, Qinghai is significantly lower than the national average for newborns (6.67%). Within the medium and high altitude regions of Qinghai Province, compared with the medium-altitude areas (altitude > 1,500 meters and ≤ 2,500 meters), the carriage rate of deafness susceptibility genes in neonates from high-altitude areas (altitude > 2,500 meters and ≤ 4,500 meters) shows a downward trend, which suggests that within the medium and high altitude range of the province, the detection rate of deafness susceptibility genes decreases with the increase of altitude. 2. Gene level: Among GJB2 gene mutations, the 235 delC gene mutation remains the most dominant type, and the detection rates of both GJB2 and GJB3 genes are lower than the national level. Notably, the detection rates of mitochondrial 12S rRNA gene mutations and SLC26A4 gene mutations in neonates from this region are both higher than the national average, with the detection rate of mitochondrial 12S rRNA gene mutations being more significantly higher. Since deafness caused by these two types of gene mutations can be effectively reduced in terms of onset risk through health education, conducting genetic testing targeting these specific genes has important clinical significance and public health value. 3. Ethnic background level: The detection rate of deafness susceptibility genes in Tibetan neonates is low, especially for the IVS7−2 A > G mutation site, and this phenomenon is more prominent in high-altitude areas. On the contrary, the detection rate of deafness susceptibility genes in Mongolian and Hui neonates in high-altitude areas shows an increasing trend.